The Impact of Income Tax on the Teaching Profession: A Debate Involving Social Justice - Ribeiro, Renato Douglas Gomes Lorenzetto [UNESP]; Soares, Daniela Alves [UNESP]; de Souza Lima, Adriana; Bezerra, Lucicleide; Frango, Edyenis (Open Book Publishers, 2022)
We present in this chapter a theoretical study and an example of teacher education practices, both inspired by the landscapes of investigation and critical mathematics education of Ole Skovsmose, as well as the mathematics for social justice of Eric Gutstein. This approach to teacher education was used with a group of undergraduate students in mathematics and Master’s students from a public university in the southeast of Brazil. The chosen theme was related to the teachers’ own issues and struggles. We explored a bill by the Brazilian Senate (445/2012), which proposes that teachers of all levels of education be exempt from paying income tax. With this programme, we intended the participants to experience landscapes of investigation in an open space for learning mathematics through a theme involving social justice, and to be able to consider the importance of this kind of approach for their own professional practice in the classroom. Based on the data produced, this chapter presents two narratives as a guiding thread for the analysis of the work carried out, showing that the assumptions of the landscapes of investigation and social justice served as a background for the teacher education proposal.